Plasticizers and Superplasticizers in Concrete Technology: Technical Performance, Market Dynamics and Sustainability Pathways in a Developing Construction Economy - Anam Hussain; Sohail Anwar; Musarrat Ullah Khan Afridi; Zeeshan Ullah (`, 2026)
Purpose: This research is a national-level assessment of the usage of plasticizers and superplasticizers in the concrete industry in Pakistan by analysing technical performance perceptions, market structure, sustainability awareness, and policy barriers. Design/Methodology/Approach: A cross-sectional survey research on 381 construction practitioners (contractors, consultants, RMC managers, suppliers, regulators, academics) was conducted using a structured Likert Scale survey instrument as a survey tool. Descriptive statistics, role-wise comparison, cross-tabulation, and Composite techno-economic analysis were made. Findings: Over 80% of the respondents confirmed that there is technical acceptance for admixture, as they said they had recently used admixture. Workability improvement was the most reliable improvement (Mean = 3.66), whilst strength improvement was considered as conditional (Mean = 3.49). Durability benefits were under-recognised (Mean = 3.15) because of poor measuring practices. Cement–admixture compatibility proved as the major technical barrier (Mean = 2.92, highest variability), side by side with inconsistent slump retention (Mean = 3.02). Economically, 87% of respondents saw that prices have been on an upward trend in the last 3 years, and the result of 3.85/5 for assessing the average cost perception shows that admixtures are generally thought to be expensive. The ensuing techno-economic adoption gap is suggestive of how positive technical performance is no guarantee for adoption in the face of price fluctuation and import dependency. While there was >70% awareness as to relevance to sustainability, cost was the overriding decision factor. Implications/Originality/Value: The study reveals that barriers to adoption in Pakistan are better explained by economic and institutional factors than technical factors. Although the performance benefits are realized, concerns of compatibility, price instability, and cost sensitivity limit low routine usage. By incorporating both market and policy-censured perceptions of performance, this research supports one of the very first empirical assessments on plasticizer and superplasticizer use at the national level in a creating conception, supplying the proof-based CU on compatibility requirements and local production respective the trace amounts of super-superplasticizer application lifecycle-centred programming. Keywords: Plasticizers, Superplasticizers, Concrete Technology, Construction Industry in Pakistan, Market Trends, Sustainable Construction.